Public Relations Strategy Komuji Creative Local Musician in Bandung - Restina Adelia; Oji Kurniadi (Bandung Conference Series: Public Relations, 2022)
Abstract. Strategi public relations Komuji, in creating the theme against covid-19, recvolution music “beda itu nada”. Difference From the musician bandung (Komuji) helped local musicians revived in building work and ekspretions. The rise of the covid, has been the biggest test the lives of musician who most of his life depends on. offair event The role of strategi public relations Komuji into the wind to create fresh for local musicians Bandung that will endure to work in the pandemic messenger. Difficult Public relation Komuji into the long for local musicians Bandung to stay productive produce piece of music. The purpose of research to know what strategy a done public relations Komuji in creative through the theme against covid-19 fixed work music recvolution “beda itu nada” of the community music mengaji Bandung (Komuji), knowcommunication public relations Komuji in creative through the theme against covid-19 fixed work music recvolution, “beda itu nada” of the community musician mengaji Bandung (Komuji), know where the obstacles that happened on strategic public relations Komuji in creative through the theme against covid-19 fixed work music recvolution, “beda itu nada” of the community musician mengaji Bandung (Komuji), considered if public relations Komuji have to strategy as solution in creative musician local Bandung on the music recvolution, “beda itu nada”. This research used the qualitative method, which is Robert K. Yin case study with type I research design that focused on a case with a unit of analysis using interviewees as the key informants of this research. Of the receipt of the technique data interview three informants , documentation , observation , and study literature available. The explained public relations Komuji strategy can creative musician local to work through the against covid-19 fixed work music recvolution, different a canting tone of the Musisi Mengaji Community (Komuji) Bandung. Abstrak. Strategi public relations Komuji, dalam menciptakan kegiatan yang bertema melawan covid-19 tetap berkarya music recvolution, beda itu nada. Dari komunitas musisi Bandung (Komuji) telah membantu para musisi lokal bersemangat lagi dalam membangunkarya dan mengekspresikannya. Maraknya wabah covid, selama ini telah menjadi cobaan terbesar bagi kehidupan para musisi yang sebagian besar hidupnya tergantung pada event offair. Adanya peranan public relations Komuji dalam menciptakan strategi menjadi angin segar bagi para musisi lokal Bandung agar tetap bertahan untuk berkarya di tengah pandemic yang serba sulit. Public relation Komuji menjadi nafas panjang bagi para musisi lokal Bandung, untuk tetap bertahan produktif dalam menghasilkan karya musiknya. Tujuan penelitian untuk mengetahui strategi apa yang dilakukan public relations Komuji dalam meningkatkan kreativitas melalui tema melawan covid-19 tetap berkarya music recvolution, beda itu nada di Komunitas Musisi Bandung (Komuji), mengetahui kegitaan komunikasi public relations Komuji dalam meningkatkan kreativitas melalui tema melawan covid-19 tetap berkarya music recvolution, beda itu nada di Komunitas Musisi Bandung (Komuji), mengetahui dimana letak hambatan yang terjadi pada strategi public relations Komuji dalam meningkatkan kreativitas melalui tema melawan covid-19 tetap berkarya music recvolution, beda itu nada di Komunitas Musisi Bandung (Komuji), mengetahui mengapa public relations Komuji harus meniciptakan strategi sebagai solusi dalam meningkatkan kreativitas musisi lokal Bandung pada program music recvolution, beda itu nada. Metode penelitian kualitatif, studi kasus Robert K. Yin desain penelitian tipe satu berfokus pada satu kasus dengan satu unit analisis menggunakan wawancara narasumber sebagai key informanpenelitian. Teknik pengambilan data wawancara tiga narasumber, dokumentasi, observasi, dan studi kepustakaan. Hasil menjelaskan strategi public relationsKomuji telah mampu meningkatkan kreativitas musisi lokal untuk berkarya melalui tema melawan covid-19 tetap berkarya music recvolution, beda itu nada di Komunitas Musisi Bandung (Komuji)